A Mechanistic Model of Microbially Mediated Soil Biogeochemical Processes: A Reality Check. Issue 6 (3rd June 2019) - Fatichi, Simone; Manzoni, Stefano; Or, Dani; Paschalis, Athanasios
Abstract : Present gaps in the representation of key soil biogeochemical processes such as the partitioning of soil organic carbon among functional components, microbial biomass and diversity, and the coupling of carbon and nutrient cycles present a challenge to improving the reliability of projected soil carbon dynamics. We introduce a new soil biogeochemistry module linked with a well‐tested terrestrial biosphere model T&C. The module explicitly distinguishes functional soil organic carbon components. Extracellular enzymes and microbial pools are differentiated based on the functional roles of bacteria, saprotrophic, and mycorrhizal fungi. Soil macrofauna is also represented. The model resolves the cycles of nitrogen, phosphorus, and potassium. Model simulations for 20 sites compared favorably with global patterns of litter and soil stoichiometry, microbial and macrofaunal biomass relations with soil organic carbon, soil respiration, and nutrient mineralization rates. Long‐term responses to bare fallow and nitrogen addition experiments were also in agreement with observations. Some discrepancies between predictions and observations are appreciable in the response to litter manipulation. Upon successful model reproduction of observed general trends, we assessed patterns associated with the carbon cycle that were challenging to address empirically. Despite large site‐to‐site variability, fine root, fungal, bacteria, and macrofaunal respiration account for 33%, 40%, 24%, and 3% on average of total belowground respiration, respectively. Simulated root exudation and carbon export to mycorrhizal fungi represent on average about 13% of plant net primary productivity. These results offer mechanistic and general estimates of microbial biomass and its contribution to respiration fluxes and to soil organic matter dynamics. Key Points: We introduce a new microbial explicit soil biogeochemistry module into a terrestrial biosphere model Uncalibrated model simulations compared favorably with global patterns of soil biogeochemistry processes Results offer mechanistic estimates of microbe contribution to soil respiration and carbon dynamics